Management Concept in Quranic Perspective - Ahmad Asrof Fitri (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2017)
This research aims to critically describe management concept of Quran that is classified into eight functions: planning, organization, staffing, coordination, leadership, motivation, communication, and supervision. This research was library research, a research using text study or literature that needs philosophical and theoretical analysis. This study used descriptive-analytical approach, by explaining Quranic verses based on several themes as classified, then analyzing them by using thematic interpretation method (tafsîr maudhû’î). The results of this study are: (1) planning has to be based on experience and strategy; (2) organization is done by division of work based on position, departments, work specialization, and chain of command with principle of helping each other; (3) in staffing, recruitment is opened to public, with several criteria: capable and trustable, diligent and knowledgeable, and good verbal communication ability; (4) coordination is implemented gradually and will success if the members consolidate; (5) leadership is expressed in three terms: khalîfah for managerial function; imâm as good example; ulî al-amr as policy maker; (6) criteria of ideal manager are democratic, polite, smart, agile, brave, having integrity, honest, and fair; (7) organization needs special division for religious and spiritual assistance to motivate all members; (8) there are four types of communication which are qaul layyin, qaul maysȗr, qaul balîgh, and qaul ma’rûf, with three phases of method: da’wah bi al-hikmah, mau’izhah hasanah, and mujâdalah bi al-latî hiya ahsan; (10) there are three types of supervision: direct and indirect performance recording, and direct inspection.